Influência da prática do futebol sobre características neuromecânicas dos pés de jovens futebolistas - Azevedo, Renato Ribeiro (2017)
Soccer is one of the most popular sports around the world. Soccer practice requires performance of different motor gestures aiming displacement, space occupation, kicking and changes of direction. Many of these gestures have been studied aiming at a proper execution to maximize performance and minimize injury risk. The high demand during training and competitions contributes to a higher frequency of injury, especially in the lower limbs. Among these injuries is the fracture of fifth metatarsal, which have not a high incidence but is considered a serious injury, mainly due to the incidence rate and the rehabilitation procedures to be adopted. Studies of adult athletes suggest that patterns of plantar pressure distribution in dynamic tasks can be related to a greater risk for fifth metatarsal injury. Additionally, some variables of proprioception and lower limb alignment also can contribute to a higher risk for injury. In this regard, could young soccer players show some adaptations that could suggest risk of fifth metatarsal fracture? The purpose of this study was to determine whether the systematic practice of soccer in young athletes affects foot neuromechanics characteristics showing relation with fifth metatarsal injury. Twenty-six young male with average age of 16 years old were divided into soccer (n=13) and a control (n=13) groups. Groups were compared regarding foot sensitivity, ankle range of motion, Q angle, and plantar pressure distribution. Plantar pressure was determined during movements of running, change of direction and jumping. Soccer group was assessed using running shoes and soccer boot, whereas controls were assessed using running shoes. Groups did not differ concerning foot sensitivity, ankle range of motion and Q angle. However, soccer group showed higher peak pressure in the lateral region of the foot, especially when using soccer boots, in comparison to controls. In summary, we found that young soccer players present a plantar pressure distribution that increase stress on the fifth metatarsal region of the foot in comparison to young not enrolled in soccer training, which may be a risk factor for injury in the adulthood.